Prophetic Values in Financial Activities - Mellisa Fitri Andriyani Muzakir; Dian Retnaningdiah; Khoirina Noor Anindya; Arief Darmawan (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2023)
This article investigates financial activities that occur in a society that adheres to an Islamic perspective (prophetic values). The method employed was a library research study that collected data, conducted analysis, compiled presentations and drew conclusions. Arisan activities are able to help improve individual welfare. However, in their implementation, many are not in accordance with the guidance of Islamic law. In addition, financial activities in the community, both taking on debt from financial institutions and non-formal organizations, can also lead to moral hazard. Therefore, every individual must be aware of the hazards or threats posed by these activities.